Hyalangiumruber sp. nov, characterization of a novel myxobacterium strain s54d21 and their secondary metabolites - Zang, Yi; Zhang, Xianjiao; Wang, Zhe; Tong, Qingyi; Zhou, Yang; Yao, Qing; Zhu, Honghui (Frontiers in Microbiology, 2024)
Myxobacteria are special bacteria with wide adaptability, which are rich sources of structurally diverse natural products with intriguing biological properties. Here, a Gram-staining-negative myxobacterium strain s54d21 T was isolated from the sediment of a wetland park in China using the Escherichia coli baiting method. Based on 16S rRNA gene sequence and genomic data, the strain was demonstrated to be a novel species of a rare genus Hyalangium, designated Hyalangium ruber sp. nov (type strain s54d21 T = GDMCC 1.1945 T = JCM 39263 T ). The subsequent chemical investigation of the strain s54d21 T led to the isolation of three rare 3,5,6-trisubstituted 2(1H)-pyrazinones namely hyalanones A-C (1-3), together with a known macrolactin A (4). Those new structures and their absolute configurations were unambiguously assigned by extensive analyses of spectroscopic data and density functional theory (DFT) calculations. In biological assays, compound 4 exhibited moderate cytotoxic activities against human cell lines RKO, A549, and NCM460 with IC50 values ranging from 27.21 to 32.14 μM.